Prediction of Detonation Velocities of Non-metal Nitrated Explosives by Simple Method - Hossein Keshavarz, Mohammad (Asian Journal of Chemistry, 2016)
A simple method is introduced for determining detonation velocities of non-metal nitrated explosives, which have significantly non-ideal behavior. The number of moles of different atoms in 100 g of pure or mixture and condensed phase heat of formation of explosives are sufficient for reliable simply prediction of detonation velocity as compared to complicated computer codes. Detonation velocities for non-metal nitrated explosives with the general formula CaHbNcOd are predicted by the equation: D (km/s) = (–3.748/r0) – 13.438a + 13.033b – 28.632c + 24.704d + 0.7265 DHf where r0 is loading density and is DHf is crystalline heat of formation. This procedure for non-metal nitrated explosives, which have non-ideal behaviour, shows good agreement with experimental values.